Endomyocardial fibrosis of the right ventricle in a patient with schistosomiasis: a case report. Issue 8 (28th July 2022) - Espinoza Romero, Cristhian; Lima, Ivna Cunha Vieira; Hotta, Viviane Tiemi; Bocchi, Edimar Alcides; Salemi, Vera Maria Cury
Abstract: Background: Endomyocardial fibrosis (EMF) is a rare and underdiagnosed cause of restrictive cardiomyopathy. Its aetiology is not yet defined and could be caused by the influence of different clinical factors that seem to combine with genetic aspects of individuals susceptible to an inflammatory process that leads to formation of fibrosis. Case summary: We describe a case of a 50-year-old man from the northeastern region of Brazil, where there is high prevalence of schistosomiasis. He presented to our centre with symptoms of right heart failure. The echocardiogram showed normal left ventricular ejection fraction. Right ventricular had normal systolic function but in the apical region was filled with a homogeneous and hypoechoic image causing obliteration and restriction of the apex. The late gadolinium enhancement with cardiac magnetic resonance showed diffuse and heterogeneous subendocardial fibrosis in the right ventricle apex consistent with EMF, but declined endocardiectomy. Discussion: This report presents an interesting case of EMF and schistosomiasis simultaneously. The hypothesis of parasitosis as a probable cause of EMF was raised by helminth-induced hypereosinophilia. Complementary imaging tests such as magnetic resonance imaging and echocardiography, in addition to clinical and epidemiological suspicion, are essential for its diagnosis. Early surgical resolution becomes crucial for long-term survival.